Deskripsi Personal Hygiene Saat Menstruasi Untuk Pencegahan Pruritus Vulva - Tria Monja Mandira; Sabrina Fitri Arli (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2026)
Background: Pruritus vulva is an itching complaint in the genital area often experienced by adolescent girls during menstruation due to inadequate personal hygiene. This condition occurs during menstruation due to moisture in the genital area. The problem in this study is how personal hygiene during menstruation affects the prevention of pruritus vulva in female students at SMPN 36 Pekanbaru. This study aims to determine the personal hygiene of adolescent girls in efforts to prevent pruritus vulva. Methods: The research method used is a descriptive quantitative design with a cross-sectional approach. The total sample size was 154 female students selected using a total sampling technique. Data collection used a questionnaire and univariate analysis. Results: The results showed that the majority of respondents (87 respondents) had adequate personal hygiene, 64 (41.56%), and 3 (1.95%) were in the good category. Conclusion : These findings indicate that the majority of female students have implemented adequate personal hygiene as a preventative measure for vulvar pruritus. It is recommended that future researchers expand the study by adding additional topics, such as knowledge and attitudes, and using an analytical design to more deeply understand the relationship between risk factors.